pengertian disiplin pengaruh disiplin kerja terhadap kinerja guru sd 352 pammanu: pengaruh disiplin kerja terhadap kinerja guru sd 352 pammanu - Haedar Haedar; Gusna Aryunita; Rezky Ramadhani (Universitas Slamet Riyadi, 2024)
This research is associative quantitative research. Associative research is research that aims to determine the relationship between two or more variables. There are 2 variables in this research, namely the independent variable is work discipline and the dependent variable is teacher performance. The population in this study were all teachers at SD 352 Pammanu, totaling 18 teachers. The method used is a direct questionnaire method, where questions and statements are given directly and specifically to the teacher. Namely to obtain valid data regarding work discipline and teacher performance. The conclusion of this research is that work discipline has a very positive and significant effect on the performance of teachers at SD 352 Pammanu.